Improving the quality of child custody evaluations : A systematic model - Tolle, Lauren Woodward (Springer New York, 2012)
Improving the Quality of Child Custody Evaluations A Systematic Model Lauren Woodward Tolle, Ph.D. and William O'Donohue, Ph.D. In the best interests of the child. This phrase has guided child custody evaluators for decades. But how do the professionals tasked with evaluation understand a child's best interests? Can it be assumed that two evaluators will come to the same decision given the same case? What evidence-based methods are-or should be-involved? Improving the Quality of Child Custody Evaluations raises significant questions of accuracy, reliability, and validity in the way even the best-intentioned evaluations are conducted, and proposes standardized guidelines for correction. Identifying conceptual as well as empirical shortcomings in the evaluation process, the authors analyze the current state of custody evaluation protocols and the welter of laws surrounding the concept of the best interests of the child. An empirically-based framework, the Egregious/Promotive Factors Model, is presented as a reliable alternative, supported by rigorous assessment tools and backed by the results of a pilot study of the model among family court judges. Throughout, the book never loses sight of the optimum end result: a reliable foundation for children's future well-being. Included in the coverage:  Current controversies in custody arrangements. Current controversies in custody guidelines. Review of the post-divorce child outcome literature. Evolution of the Egregious/Promotive Factors Model (EPFM). Assessing risk and positive factors in parenting. Preliminary support for the EPFM.